Analysis of the variability of precipitation in front of land use changes in the municipality of Tucuruí-PA (Research, Society and Development, 2020)
This article aims to analyze the variations in precipitation, as well as the spatial dynamics of land use and coverage in Tucuruí, southeastern state of Pará, from 1980 to 2015. For this, data from meteorological stations of the National Institute were used. Of Meteorology (INMET) and the National Water Agency (ANA) for the study of precipitation in the municipality, Mann-Kendall and Sen’s Slope tests were used, for the 95% significance level. To understand the changes in land cover in the study area, the linear mixture model in Landsat-TM 3, 5 and 8 segmented images was used, for multitemporal analysis of the land cover classes identified in the municipality. The results indicated that there were no trends in the series of annual precipitation totals (1980 to 2015). However, there were significant variations in the interannual rainfall regime, with an average annual rainfall of 2431.6mm. The data indicated seasonality characterized by two distinct seasons: less rainy, between the months of June to November; and the other more rainy, between the months of December to May. The mapping showed different classes of land use in the period studied, however the classes of native vegetation, secondary vegetation, hydrography and exposed soil showed non-linear spatio-temporal variation, however the class of exposed soil showed an increasing behavior since 1980 with beginning of the hydroelectric plant works. Regarding the annual rainfall of the municipality, it is noted that there is no direct relationship with the classes of land use and coverage in the years analyzed.